Síntese de derivados de naftoquinonas com potencial atividade biologica. - Raquel Geralda Isidório (2022)
The naphthoquinones are substances widely distributed in nature and are endowed with diverse biological activities, such as antifungal, antibacterial, anti-inflammatory, antiplasmodial, trypanocidal and antitumor. Lapachol and lawsone are important representatives of this class of bioactive substances. The interest in their biological activities has motivated the preparation of derivatives and synthetic analogues by research groups worldwide. Therefore, in this thesis work, was conducted the synthesis, starting from lawsone (2-hydroxy-1,4-naphthoquinone), of eleven new derivatives: eight glycosyltriazoles and three derivatives of ortho-furanonaphthoquinones. The glycosyltriazoles were prepared from a [2+3] cycloaddition reaction between peracetylated glycosyl azides, derived from D-glucose, D-galactose, D-N-acetylglucosamine and L-fucose, and 3-C-propargyl-lawsone. Removal of the acetyl groups provided the equivalent deacetylated derivatives. To obtain the orthonaphthoquinone derivatives, the 3-C-allyl-lawsone was initially converted into the 2-methyl2,3-dihydrofuran-1,2-naphthoquinone derivative, which, by reaction with N-Bromo succinimide, provided the 2-bromomethylnaphtho[1,2-b]furan-4,5-dione. The abovementioned, upon reaction with sodium azide, provided the corresponding azide. Alternatively, the 3-C-allyl-lawsone was converted into the 2-iodomethyl-2,3-dihydrofuran-1,2- naphthoquinone derivative, which was subjected to a series of chemical reactions in which isomerization of the starting ortho-naphthoquinone was observed for the corresponding paranaphthoquinone. In addition to the new derivatives, eighteen naphthoquinone intermediates were synthesized, including an O- and C-allyl derivative of lawsone, as well as a 3,3- dialylated derivative, probably resulting from the Claisen rearrangement of the O,Cdialkylated product. An anthraquinone was also obtained during the reaction of lawsone with propionaldehyde in the synthesis of 2-methylnaphtho[1,2-b]furan-4,5-dione. The antiplasmodial, antifungal, antibacterial, leishmanicidal and cytotoxic activity against some tumor cell lines (B16-F10, C6, A549) of several substances obtained during this work was evaluated and some substances showed activity in the low micromolar range (IC50 lower than 5 µM) and even submicromolar, reinforcing the importance of the naphthoquinone class as key structures for drug development.